2019
DOI: 10.3892/ol.2019.9910
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis with regard to PD‑L1 and CD155 expression in human small cell lung cancer and a comparison with associated receptors

Abstract: Immune checkpoints expressed on tumor cells may suppress the cytotoxicity of tumor-infiltrating lymphocytes (TILs) via interaction with their ligands. In the present study, checkpoint proteins and ligands, including programmed death-1 (PD-1), programmed death ligand-1 (PD-L1), cluster of differentiation (CD)155 and T cell immunoreceptor with immunoglobulin and ITIM domains (TIGIT) were systematically analyzed in patients with small cell lung cancer (SCLC). Furthermore their clinicopathological features and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…As shown in Fig. 1a, PVR expressed in head and neck cancer (HNSC), lung adenocarcinoma (LUAD) and stomach cancer (STAD), which was consistent with the previous study [13,15,33]. In addition, it also expressed across a broad spectrum of cancers including bladder cancer (BLCA), endometrioid cancer (UCEC), esophageal cancer (ESCA), kidney chromophobe (KICH), Kidney papillary cell carcinoma (KIRP), prostate cancer (PRAD), thyroid cancer (THCA), and especially in colon cancer (COAD) and rectal cancer (READ) within 50 datasets.…”
Section: The Expression Analysis Of Pvr In Tumor Tissues and Cell Linessupporting
confidence: 92%
“…As shown in Fig. 1a, PVR expressed in head and neck cancer (HNSC), lung adenocarcinoma (LUAD) and stomach cancer (STAD), which was consistent with the previous study [13,15,33]. In addition, it also expressed across a broad spectrum of cancers including bladder cancer (BLCA), endometrioid cancer (UCEC), esophageal cancer (ESCA), kidney chromophobe (KICH), Kidney papillary cell carcinoma (KIRP), prostate cancer (PRAD), thyroid cancer (THCA), and especially in colon cancer (COAD) and rectal cancer (READ) within 50 datasets.…”
Section: The Expression Analysis Of Pvr In Tumor Tissues and Cell Linessupporting
confidence: 92%
“…A total of 20 full-text articles were excluded for the following reasons: 12 lacked necessary information, three were editorials, two were letters, two did not report using an IHC method, and one was a review. Finally, nine articles (8)(9)(10)(11)(12)(13)(14)(15)(16) published between 2015 and 2019 were included in this meta-analysis. The selection flowchart is displayed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…The baseline characteristics of the included studies are shown in Table 1. Five studies were performed in China (11,(13)(14)(15)(16), two in Japan (8,9), and one each in Taiwan (10), and Italy (12), respectively. The total sample size was 921, ranging from 40 to 205.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations